Phoenicians in the Mediterranean: diversified forms of contact - Nicolau Kormikiari, Maria Cristina (Cadernos do LEPAARQ (UFPEL), 2018)
In this article we approach the most recent developments on the research regarding the Phoenicians, a people who inhabited the coastal plains of eastern Mediterranean. We also approach the developments regarding their territorial expansion, especially towards the very opposite region in relation to their homeland: the western shores of the Mediterranean. We also discuss the pertinence of the use of such concepts as pre-colonization and colonization and present the position of some archaeologists drawn out of the Post-Colonial Theories. RESUMO: Neste artigo abordamos as mais recentes sistematizações acerca dos fenícios, povo habitando a costa oriental da Bacia do Mediterrâneo, e acerca de seus processos de expansão territorial, notadamente nas regiões central e ocidental desta mesma Bacia. Discutimos a pertinência do uso de conceitos como pré-colonização e colonização e os questionamentos que alguns arqueólogos têm feito a estes, com base nas Teorias Pós-coloniais